Protein Kinase Inhibitors CK59 and CID755673 Alter Primary Human NK Cell Effector Functions - Scheiter, Maxi; Bulitta, Björn; van Ham, Marco; Klawonn, Frank; König, Sebastian; Jänsch, Lothar (Frontiers in Immunology, 2013)
Natural killer (NK) cells are part of the innate immune response and play a crucial role in the defense against tumors and virus-infected cells. Their effector functions include the specific killing of target cells, as well as the modulation of other immune cells by cytokine release. Kinases constitute a relevant part in signaling, are prime targets in drug research and the protein kinase inhibitor Dasatinib is already used for immune-modulatory theraphies. In this study, we have tested the effects of the kinase inhibitors CK59 and CID755673. These inhibitors are directed against CaMKII (CK59) and PKD family kinases (CID755673) that were previously suggested as novel components of NK activation pathways. Here, we use a multi-parameter, FACS-based assay to validate the influence of CK59 and CID755673 on the effector functions of primary NK cells. Dose dependent treatment with CK59 and CID755673 indeed results in a significant reduction of NK cell degranulation markers and cytokine release in freshly isolated PBMC populations from healthy blood donors. These results underline the importance of CaMKII for NK cell signaling and suggest PKD2 as a novel signaling component in NK cell activation. Notably, kinase inhibition studies on pure NK cell populations indicate significant donor variations.